SUBJEKTIVITAS RENDRA DALAM MENGKRITISI PEMBANGUNAN MELALUI POTRET PEMBANGUNAN DALAM PUISI - , Happy Merdikowati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research identified the subjectivity of Willibrodus Surendra Broto as known as WS. Rendra and how Rendra's passion in critize the developmemt that mirrored in grathered of rhyme the \"Potret Pembangunan dalam Puisi\". Trough the study of art psychology especially using Lacan psycholoanalysis theory. The researchment to Rendra before is always skip the subjectivity that represented in rhyme masterpiece. The research used the concept subjectivity that explained by Jaques Lacan where in structure the subjectivity always passes three structure trajectories, which are Real, Imajiner and Symbolic. In Real structure, a subject will get fullfillment, while Imajiner the subject separated from the fullfillment and starting to know the request because the existence of insuffiency. While the request expressed not only trough verbal, but also from action. In symbolic structure, a subject never can be released from language. Where the searching progress of ideal ego expressed by symbolic and often had misunderstanding. In this perspective, the subjectivity of Rendra will be perceived. Method that used for researching the subjdctivity of \"Potret Pembangunan dalam Puisi\" used the method of Lacan psychoanalysis. This method comes from Lacan theory that identity the subject in society created from the other subject. Where the subject built from passion. The pattern of passion concept as like as identity of the subject. In meaning case, Lacan spelled that a meaning which it connected with the other meaning. So did the subject and the passion. Perceived art masterpiece using Lacan perspective is the effort of to find subconscious condition that full of feeling the lack and lost which are bringing the passion for unity self. This method used to what happened in art masterpiece language as fas as art language moving out from thr author, trough metafora phenomenomn and metomini that are inside. The result of this research showed there were any critism and ideal egos to develop of Rendra subjectivity in \"Potret Pembangunan dalam Puisi\". From indication of passion, Rendra sided to marginal people, linked the government power as the cause of society suffer and make liyan as the directive for creating the ideal ego.